2019
DOI: 10.1590/2237-6089-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

Reflective function and identity in adolescents with clinical and nonclinical symptoms

Abstract: Introduction Reflective function is developed in the context of secure attachment and corresponds to the ability to understand one’s mental states and those of others. Thus, identity develops, which relates to the experience of self as unique, continuous and coherent. Objective To identify reflective function and identity features in adolescents with clinical and nonclinical symptoms of mental health problems. Method Participants were 188 Brazilian high school students aged 14-17 years: 30.3% with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…According to our results, hypomentalization was positively associated with borderline personality features and emotional dysregulation in adolescents. Our findings are consistent with the previous works showing that mentalization deficits are correlated with emotional dysregulation (Gambin et al, 2021;Marszał & Jańczak, 2018), and borderline personality features (Both et al, 2019;Quek et al, 2017). Our results support the BPD metallization model and also Linehan's BPD model, emphasizing on the role of breaks in mentalizing and emotional dysregulation in BPD development (Fonagy & Luyten, 2009;Linehan et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…According to our results, hypomentalization was positively associated with borderline personality features and emotional dysregulation in adolescents. Our findings are consistent with the previous works showing that mentalization deficits are correlated with emotional dysregulation (Gambin et al, 2021;Marszał & Jańczak, 2018), and borderline personality features (Both et al, 2019;Quek et al, 2017). Our results support the BPD metallization model and also Linehan's BPD model, emphasizing on the role of breaks in mentalizing and emotional dysregulation in BPD development (Fonagy & Luyten, 2009;Linehan et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have examined the role of mentalization in adolescent identity development. In a recent study 30 , reflexive function has been found inversely associated with adolescents' identity conditions characterized by discontinuity and inconsistency. These results confirm that reflexive function constitutes a fundamental component of identity and that lack of mentalization significantly interferes with identity integration.…”
Section: The Importance Of Imagining What Others Think: Mentalization...mentioning
confidence: 89%
“…In Mexico ( 38 ), the inventory was tested with adolescents engaged on criminal activity, finding significant results in comparison with healthy controls. In Brazilian population ( 39 ), with adolescents reporting psychiatric symptoms with the Strength and Difficulties Questionnaire and impairment on reflective functioning ( 34 ), findings were significant differences with adolescents who reports better psychological adjustment. In Austrian population, significant differences were found between adolescents with internet addiction and problematic internet use and healthy controls ( 40 ).…”
Section: Introductionmentioning
confidence: 99%